A violent legacy: policing insurrection in South Africa from Sharpeville to Marikana - Dixon, Bill (Oxford University Press, 2015)
Fifty-two years separate the fatal shootings by police of 69 anti-apartheid protestors at Sharpeville on 21st March 1960 and of 34 striking miners at Marikana on 16th August 2012. The parallels between the two ‘massacres’ are easy to overstate; but both involved the use of lethal violence by the police against people taking part in insurrectionary action. Drawing on Marenin’s (1982) work on the relative autonomy of the police, this paper argues that events at Marikana have to be seen in the context of South Africa’s failure to tackle the structural violence of apartheid and the use of direct, personal violence by the police before and since the country became a constitutional democracy in 1994.